2012
DOI: 10.1155/2012/624692
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for Lower Urinary Tract Symptoms and Quality of Life in Elderly Patients with Benign Prostate Hypertrophy: A Randomized Controlled Trial

Abstract: Tai chi exercise has been recommended as suitable for the improvement of health in the elderly. The purpose of this study was to investigate the effects of tai chi on lower urinary tract symptoms (LUTSs), quality of life (QoL), and sex hormone levels in patients with benign prostate hypertrophy (BPH). The elderly patients with BPH were randomized to receive tai chi or usual care. Fifty-six participants were randomized into either the tai chi group (n = 28) or the control group (n = 28). After 12 weeks of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
19
1
1
Order By: Relevance
“…There were no differences in the basal levels of total testosterone and of free testosterone among the participants. Testosterone levels have been shown to increase among elderly patients with benign prostate hypertrophy after Tai Chi training for a year (15). In the present study, nevertheless, Tai Chi exercise training did not affect the basal level of testosterone among our healthy participants.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…There were no differences in the basal levels of total testosterone and of free testosterone among the participants. Testosterone levels have been shown to increase among elderly patients with benign prostate hypertrophy after Tai Chi training for a year (15). In the present study, nevertheless, Tai Chi exercise training did not affect the basal level of testosterone among our healthy participants.…”
Section: Discussioncontrasting
confidence: 73%
“…Groups of Chinese have practiced Tai Chi exercise in the early morning since the 12 th century and continue to do so in large numbers. Tai Chi exercise is a moderate intensity exercise and was believed in ancient China to be better adapted to people who are middle-aged or older (15). The characteristics of Tai Chi exercise consists of breathing exercises that are matched to slow meditative and graceful movements that simulate the postures of various animals in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 50 studies in Table 1, no serious AEs related to Tai Chi was reported, and 32 studies 18, 20, 21, 26-29, 31-34, 36-39, 41-44, 50-52, 55-57, 59-65 reported no occurrence of any AEs related to intervention. Fifteen 16, 17, 19, 23-25, 30, 45, 47-49, 53, 54, 58, 59 of the 50 studies specifically reported occurrences of minor musculoskeletal aches and pain, with complaints of lower extremity pain (knee and ankle) being most common.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis, containing 19 studies, reports a positive association between Body Mass Index (BMI) and Lower urinary tract syndrome (LUTS) related to BPH (odds ratio (OR) = 1.28%) (Wang, Mao et al 2012). Many investigations have shown that obese men have a higher risk of BPH (Wang, Hsieh et al 2011, Corona, Vignozzi et al 2014 and proved that the impact on male aging can be halted by aerobic exercise (Brown and Emberton 2009, Poon and McVary 2009, Jung, Lee et al 2012, Lee, Kim et al 2014.…”
Section: Introductionmentioning
confidence: 99%